Financial Development and Health Outcomes: Do Financial Globalization Matter in Selected Asian Economies? - Shi, Guoxin; Wang, Dawei; Altuntaş, Mehmet (Frontiers in Public Health, 2022)
The importance of health is well documented in the development economics literature because of its increasing effects on economic growth in the long-run. Financial development and financial globalization are essential resources for health. This study examines the role of financial development and financial globalization in the rapid rise of life expectancy in China, India, and Pakistan by using the annual data covering the period of 1991–2019. The ARDL bounds testing approach confirm the long-run relationship between financial development, financial globalization, and life expectancy in the presence of GDP, health expenditure, and the internet. The long-run findings indicate that financial development positively affects life expectancy by 0.599% in China. The novel findings also indicate that financial globalization positively affects life expectancy by 1.247% in Japan and 1.121% in India. Our findings offer new empirical insights to policymakers crucial to improving life expectancy in China, India, and Japan.